2022
DOI: 10.3390/horticulturae8080738
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Best Planting Season for the Protected Cultivation of Papaya

Abstract: Papaya is a tropical crop increasingly cultivated in the greenhouses of subtropical regions such as South East Spain, where the determination of the best planting season is important to ensure a stable fruit production and quality during the year. In this work, we studied plant growth, yield, and fruit quality, comparing spring and autumn planting seasons in ‘Intenzza’ cultivar. The results showed that planting in spring favors plant growth, leading to an earlier entry into production. Total yield and fruit qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, 'BH-5' and 'Red Lady' were the worst adapted to the growing conditions due to the high incidence of pentandric, carpelloid, and male flowers, which gave fruits without commercial value. In the same context, Salinas et al (2022) reported up to 100% of male flowers from hermaphrodite plants of the 'Intenzza' cultivar in autumn (November) and predominantly in all seasons except in May (spring), recording a maximum temperature of 36.6 °C in July in a greenhouse with natural ventilation. Based on these findings, they recommend transplanting in February or March to achieve good yields.…”
Section: Resultsmentioning
confidence: 91%
“…However, 'BH-5' and 'Red Lady' were the worst adapted to the growing conditions due to the high incidence of pentandric, carpelloid, and male flowers, which gave fruits without commercial value. In the same context, Salinas et al (2022) reported up to 100% of male flowers from hermaphrodite plants of the 'Intenzza' cultivar in autumn (November) and predominantly in all seasons except in May (spring), recording a maximum temperature of 36.6 °C in July in a greenhouse with natural ventilation. Based on these findings, they recommend transplanting in February or March to achieve good yields.…”
Section: Resultsmentioning
confidence: 91%
“…The fruit was harvested in July 2018, owing to a short juvenile phase [ 5 ], and was categorized into 3 ripening stages based on weeks after anthesis (WAA), according to Zuhair, Aminah, Sahilah, and Eqbal [ 11 ]: (1) unripe at 16 WAA, (2) half-ripe at 18 WAA, and (3) full-ripe at 20 WAA. At each stage, a total of nine fruits were harvested in three biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Papaya originated from the lowland of Mexico to Panama and is found primarily in tropical regions between 23° N and S latitudes because the cultivation requires high temperatures year-round [ 2 ]. Subtropical regions, including Mediterranean countries, can also cultivate papaya; some of these regions have to use protected facilities, including a greenhouse, because low temperatures during winter affect fruit set, growth, and production [ 3 , 4 , 5 ]. Recently, due to the increasing demand for papaya and the changing climate, the cultivation has expanded to temperate regions such as Far East Asia [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Papaya originated from the lowland of Mexico to Panama and is found primarily in tropical regions between 23 °N and S latitudes because the cultivation requires high temperatures year-round (Daagema et al ., 2020). Subtropical regions, including Mediterranean countries, can also cultivate papaya; some of these regions have to use protected facilities, including a greenhouse because low temperatures during winter affect fruit set, growth, and production (Gunes and Gübbük, 2012; Salinas et al ., 2019; Salinas et al .,2022). Recently, papaya cultivation has expanded from subtropical and tropical regions to temperate regions, including Japan and the Republic of Korea, owing to increasing average temperature and consumer needs (Jeon et al ., 2022; Jeong et al ., 2020; Ogata et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%